Progesterone and VIP cross-talk enhances phagocytosis and anti-inflammatory profile in trophoblast-derived cells - Vota, Daiana Marina (2017)
Trophoblast cells produce several inmmuneregulators like the Vasoactive Intestinal Peptide (VIP) and P4 targeting multiple circuits, and also display an intese phagocytic ability allowing embryo implantation in a tolerogenic context. Here, we explored whether P4 and VIP- crosstalk modulates trophoblast cell function, focus on the phagocytic ability and the immune homeostasis maintenance. P4 enhanced the phagocytosis in trophoblast-derived cells quantified by the engulfment of latex-beads or eryptotic erythrocytes. P4 and VIP modulated the balance of anti/pro-inflammatory mediators, increasing TGF-β expression, with no changes in IL-1, IL-6, or nitrites production. This modulation was accompained by transcription factor expression changes that could turn on tolerogenic programs represented by increased PPAR-γ and decreased IRF-5 expression. Finally, P4 stimulated VPAC2 expression in trophoblast cells and VPAC2 over-expression enhanced phagocytosis mimicking P4-effect. Therefore, P4 and VIP network enhances the phagocytic ability of trophoblast-derived cells, through a mechanism involving VPAC2 accompained with an anti-inflammatory context.